Similar erythrocyte sedimentation rate and C-reactive protein sensitivities at the onset of septic arthritis, osteomyelitis, acute rheumatic fever - Jonathan E. Reitzenstein; Loren G. Yamamoto; Hareesh Mavoori (MDPI AG, 2010)
The erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are employed in the evaluation of patients with suspected septic arthritis, osteomyelitis, and acute rheumatic fever. The purpose of this study is to determine if one test has greater sensitivity (rises earlier) than the other. Laboratory data were retrieved for pediatric patients hospitalized with one of the above three conditions, who had both ESR and CRP tests done on or shortly prior to admission. Sensitivity calculations were performed for mild, moderate, and severe degrees of ESR and CRP elevation. Microcytic erythrocytes, as defined by mean corpuscular volume (MCV) less than 80 μL, were identified to see if this affects the ESR. ESR or CRP sensitivities depend on the cutoff value (threshold) chosen as a positive test. The sensitivities were similar for similar degrees of elevation. ESR and CRP discordance was not significantly related to MCV. We concluded that the CRP does not rise earlier than the ESR (their sensitivities are similar). Previously published conclusions are dependent on arbitrary thresholds. We could not find any evidence that MCV affects the ESR.